2022
DOI: 10.1177/1934578x221115511
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Inhibits Trypsin Activity and Suppresses the Growth of Colorectal Cancer in Vitro and in Vivo

Abstract: Colorectal cancer (CRC) is a malignant tumor with high incidence and bad prognosis. Therapies, which are more safe and effective, are urgently needed. Trypsin is proved to be crucial to cancer proliferation and migration, therefore, it is possible to control cancers by modulating its activity. Fisetin is a flavone with trypsin inhibition properties that was screened from more than 45 compounds derived from traditional Chinese medicine (TCM). However, the effects and mechanisms of fisetin on CRC have not been w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Fisetin suppressed HCT116 induced tumor growth in NOD/Shi-scid-IL2R gamma (null) (NOG) mice in a dose-dependent manner compared to control group [218]. Another study showed that due to poor water solubility, the fisetin micelles, composed of poly(ethylene glycol)-poly(ε-caprolactone), i.e., MPEG-PCL, are more efficient antitumor agents over free fisetin as tested in CT-26 tumor model.…”
Section: Fisetinmentioning
confidence: 99%
“…Fisetin suppressed HCT116 induced tumor growth in NOD/Shi-scid-IL2R gamma (null) (NOG) mice in a dose-dependent manner compared to control group [218]. Another study showed that due to poor water solubility, the fisetin micelles, composed of poly(ethylene glycol)-poly(ε-caprolactone), i.e., MPEG-PCL, are more efficient antitumor agents over free fisetin as tested in CT-26 tumor model.…”
Section: Fisetinmentioning
confidence: 99%
“…51 Li et al conducted both in vitro and in vivo experiments and found that fisetin remarkably inhibited colorectal cancer cell proliferation and migration, induced cell cycle arrest and apoptosis, and suppressed tumor growth in tumor-bearing mice. 52 Additionally, Jia et al investigated the in vivo antitumor effect of fisetin in a pancreatic cancer model and identified the enhancement of the AMPK/mTOR signaling pathway after fisetin treatment. 53 Li et al explored the effects of fisetin in a metastatic breast cancer xenograft model and observed significant inhibition of primary tumor growth and reduction in lung metastasis.…”
Section: Research Progress Of Fistein and Its Antitumor Effects On An...mentioning
confidence: 99%
“… 51 Li et al conducted both in vitro and in vivo experiments and found that fisetin remarkably inhibited colorectal cancer cell proliferation and migration, induced cell cycle arrest and apoptosis, and suppressed tumor growth in tumor-bearing mice. 52 …”
Section: Research Progress Of Fistein and Its Antitumor Effects On An...mentioning
confidence: 99%
See 1 more Smart Citation